INTERPRETING MORAL VALUE IN UP-FILM - Surya Tanandjaja, Michael; Winardi, Yohanes Kurniawan; Trihastutie, Nopita (ELite Journal : International Journal of Education, Language and Literature, 2024)
This research aims to analyze the moral value of Up Film. This film was made in 2009 by Pete Docter. This research applies a pragmatic approach to understanding the genre of literary works by explaining the author’s unique aim to the reader. This research used a descriptive qualitative method to acquire in-depth information and cover social reality based on the parameters of the research subject. The findings show that the film has the moral value of the Up film which consists of courage, honesty, respect, and love. There is an ethical value related to the concept of family which consists of loyalty and sacrifice. In conclusion, the moral values in Up film instill in viewers the fortitude to move forward in the face of adversity and loss. The concept of family is also portrayed in a profound and poignant Up film, demonstrating that family is not just defined by blood ties but also by love, affection, and support from one another.